2013
DOI: 10.1088/0268-1242/28/2/025010
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected surface implanted layer in static random access memory devices observed by microwave impedance microscope

Abstract: Abstract. Real-space mapping of doping concentration in semiconductor devices is of great importance for the microelectronic industry. In this work, a scanning microwave impedance microscope (MIM) is employed to resolve the local conductivity distribution of a static random access memory (SRAM) sample. The MIM electronics can also be adjusted to the scanning capacitance microscopy (SCM) mode, allowing both measurements on the same region. Interestingly, while the conventional SCM images match the nominal devic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…MIM has been applied successfully to measure conductivity inhomogeneity in a wide variety of systems, including carbon nano-tubes [3], graphene [4], In 2 Se 3 nanoribbons [5], quantum hall edge states [6], MoS 2 field effect transistors [7], and more [8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…MIM has been applied successfully to measure conductivity inhomogeneity in a wide variety of systems, including carbon nano-tubes [3], graphene [4], In 2 Se 3 nanoribbons [5], quantum hall edge states [6], MoS 2 field effect transistors [7], and more [8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the MIM‐Im signal is proportional to the area of Te‐SP. On the other hand, the MIM‐Im signal is also a monotonic function of the sample conductivity, which is used to reflect the doping concentrations in semiconductors . Owing to the macro‐segregation and the impurity gettering effects, impurities tend to aggregate in the largest Te‐SP particles, which are the last to freeze.…”
Section: Resultsmentioning
confidence: 99%
“…However, the effects of Te‐SP particles and extended on electronic inhomogeneity were not resolved. Near‐field scanning microwave impedance microscope (MIM) is a noncontact and nondestructive technique for characterizing both topographical and local electronic properties, which has demonstrated great potential for the application in two‐dimensional and nano‐materials, biology and IC chips , etc. The microwave electronics detect the real and imaginary components of the effective tip‐sample impedance and output as MIM‐Re and MIM‐Im signals, which contain the local dielectric and conductivity ( ϵ , σ ) information of the material .…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 67, the authors demonstrated the MIM experiments on a static random-access memory (SRAM) sample to resolve the local conductivity distribution. They showed the microwave imaging on the staircase and SRAM samples in the linear impedance.…”
Section: Quantitative Measurements Of Nanoscale Permittivity and Condmentioning
confidence: 99%